ASPEK SOSIAL DALAM NOVEL PARTIKEL KARYA DEWI LESTARI: TINJAUAN SOSIOLOGI SASTRA - Anik Aniswanti; Sri Wahyuningtyas (CARAKA, 2016)
The aims  of this  study  was  to  describe  (1)  the  structure  of  novel  that  include characters and characterization, background, and plot, (2) social aspects, (3) social change the main character in the novel Partikel of Dewi Lestari. Types of research is qualitative research. This study data in the form of units of paragraphs or discourse in the novel Partikel. Data source in this research novel Partikel of Dewi Lestari. This research use instrument equipped concept or theory characters and characterization, background, plot, social aspects, and social change. Method of collecting this research use formal methods, to read the whole novel. Data collection technique this research in a way to read the whole novel, observe, and notes data obtained from data card. Data analysis methods is qualitative methods. Data analysis technique use descriptive qualitative. The results of this study show novel Partikel related element. The results which is obtained. (1) The structure of novel that (a) include characters and characterization of novel Partikel is Zarah main character and additional figures is Firas, Aisyah, Koso, Paul, Storm and Simon Hardiman. Figure Zarah be told as a desperate man (b) background in novel Partikel is Batu Luhur, Kebun Raya Bogor, Bukit Jambul, and background times is morning, evening, night, social background is social on, social medium, and lower social, (3) and plot in novel Partikel groove mix (2) social aspects in novel Partikel aspect of love that include love of family, love of best friend, love of girl or boyfriend, cultural aspect is Sundanese culture and western culture (3) social change the main character in the novel Partikel of Dewi Lestari changes desired when Zarah decided to work on a Tanjung Puting, change is not desired when loss of harmony, fast change when Zarah receive the Nikon camera’s, slow changes when decide school, small change when Zarah decide formal school, and big change when Zarah join in The A-Team.